MEDIA SCRAMBLE UNTUK EDUKASI PENCEGAHAN KARIES GIGI PADA ANAK SEKOLAH DASAR: STUDI DI NAMIRA ISLAMIC SCHOOL - Berliana Sari; Syahira Syahda (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
According to the Ministry of Health Regulation No. 17 of 2023, health is a state of physical, mental, social, and spiritual well-being that enables individuals to live productively. Oral health is part of promotive and preventive efforts to prevent dental and oral diseases, including dental caries, which frequently occurs in elementary school children and can affect their growth and quality of life. Lack of understanding among children about oral health is a risk factor for caries. Therefore, interactive and engaging educational methods such as scramble media are needed to improve children's understanding of maintaining oral health. This study aimed to describe the use of scramble media in dental caries prevention education among third-grade students at Namira Islamic School. This research used a quantitative descriptive approach involving 30 third-grade students. Data were collected through observation and a knowledge assessment instrument administered before and after education using scramble media. Before the education, students with good knowledge were 6 (20%), moderate 19 (63.3%), and poor 5 (16.6%). After the education, students with good knowledge increased to 19 (63.3%), moderate 11 (36.6%), and there were no students in the poor category (0%). Dental caries prevention education using scramble media is effective in improving elementary school students' knowledge of oral health and can serve as an alternative promotive and preventive educational method in schools.